Effects of bodybuilding training on heart rate regulatory systems in normal-weight and overweight adolescents - Oleh Pahulych; Igor Grygus; Alla Aloshyna; Yurii Valetskyi; Eduard Syvokhop (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. To investigate the characteristics of changes in the activity of heart rate regulatory systems in normal-weight and overweight adolescents performing various training regimens during bodybuilding training. Material & Methods. 80 adolescents aged 14–15 were examined. Participants in Group A (40 boys) had a baseline body fat percentage (BF%) of 15.1%. Group B comprised 40 overweight participants, with a body fat percentage of 39.8%. There were no statistically significant differences in height between the participants in the study groups. During the 12-week bodybuilding programme, participants in subgroups A1 and B1 followed a low-intensity training regimen (Ra=0.57). Participants in subgroups A2 and B2 followed a high-intensity training regimen (Ra=0.71). The heart rate variability method was used to assess functional reserves and adaptive capacity. Baseline body fat percentage was assessed using bioelectrical impedance analysis. Results. After 12 weeks of bodybuilding training, the basal activity of heart rate regulatory systems decreased by 10-fold in members of subgroup A2 (LF/HF –58.8%) compared with subgroup A1. At the same time, adolescents in subgroup A1 showed an increase in the central regulatory circuit of the sinus rhythm (VLF +3.2%). In contrast, participants in subgroup A2 exhibited a 6.7% reduction in baseline VLF against a background of increased parasympathetic activity (LF +20.5%). In response to the exercise test, participants in subgroup A1 exhibited a shift in the autonomic balance towards sympathetic regulation (LH/HF +23.1%) accompanied by an increase in VLF (+4.4%). In participants of subgroup B1, an increase in LF/HF (+5.3%) was recorded against a background of increased LF (+7.5%). Meanwhile, in subgroup B2, a shift in the autonomic balance towards parasympathetic regulation (LF/HF –42.1%) was observed. In response to the exercise test, subgroup B1 participants showed not only a shift in autonomic balance towards sympathetic regulation (LF/HF +19.5%), but also an increase in the central regulatory circuit of the sinus rhythm (VLF +12.1%). An increase in vagal influence on the sinus node (LF/HF –9.2%) was observed in the adolescents in subgroup B2 in response to the exercise test. Conclusions. The study results showed that using high-intensity exercise (Ra=0.71) during extended bodybuilding training helped to reduce the heart rate regulatory load in overweight adolescents. Such adaptive and compensatory responses occurred both at rest and after the exercise test. These findings indicate pronounced long-term adaptation accompanied by increased functional reserves and enhanced adaptive capacity. Under a low-intensity training regimen (Ra=0.57), overweight adolescents enhanced the central regulatory circuit of the sinus rhythm during a bodybuilding training programme. At the same time, such changes occur against the background of a shift in autonomic balance towards sympathetic regulation, which, under certain conditions, indicates not only the activation of the body’s compensatory responses to a physical load but also possible manifestations of non-functional overexertion.